DISTRIBUSI PERAKARAN KELAPA SAWIT DAN SIFAT FISIK TANAH PADA UKURAN LUBANG TANAM DAN APLIKASI TANDAN KOSONG SAWIT YANG BERBEDA - Pradiko, Iput; Hidayat, Fandi; Darlan, Nuzul Hijri; Santoso, Heri; Winarna, Winarna; Rahutomo, Suroso; Sutarta, Edy Sigit (Jurnal Penelitian Kelapa Sawit, 2016)
This study was conducted to determine the root distribution and to analyze soil physical factors that affect roots development in different size of planting hole; standard (0.6 m x 0.6 m x 0.6 m), medium ((1 x 1 cm x 0.6 m) with 400 kg empty fruit bunches (EFB)/hole and 740 g urea/hole, and big (2.8 mx 2.8 mx 1 m) with 400 kg EFB/hole and 740 gr urea/hole. This study employed demonstration plot that used a non factorialrandomized block design (RBD) with three treatments (standard, medium, and big hole) and three replications. The results showed that total distribution of oil palm roots in standard, medium, and big planting 3 3 hole are respectively 28.60 g /dm ; 26.69 g/dm ; and 3 24.47 g/dm . Types of planting hole did not significantly affect primary root, but significantly affected secondary and tertiary root distribution. In big planting hole, oil palm has highest secondary and tertiary roots distribution than the others (up to 70%). Increasing ofpermeability, porosity, and decreasing of soil bulk density tends to increase root distribution, especially tertiary. Meanwhile, increase on soil water content is not followed by secondary and tertiary distribution, since booth root types more distributed in the upper soil layer. Better soil tillage; through big planting hole, can improve soil properties and optimizing development of secondary and tertiary roots.